(untitled) (Research, Society and Development, 2020)
Introduction: Domestic violence suffered by women is a global public health problem that causes a series of negative commitments in the victim’s life. Objective: To identify through the scientific literature how social isolation can contribute negatively to the increase in the rate of domestic violence. Methodology: This is a study with a qualitative approach, of the integrative review type, whose database was the Virtual Health Library Nursing using the Health Sciences Descriptors (DeCS) Social Isolation; Domestic violence; Women’s Health. Complete articles were selected, in Portuguese and English, published between 2010 and 2020. At the end of the application of the criteria, 8 articles emerged for thorough reading and content production. Results: In the data analysis, two categories were established: Domestic Violence and Impacts generated by violence in the victim’s life. Final Considerations: The research led us to conclude that social isolation is a predisposing factor for domestic violence against women, the team cannot be limited to receiving complaints, as the victims need guidance, clarification about their rights and possible choices of available health services.